Investigating the role of mobile health in epilepsy management: A systematic review - Atefeh Khoshkangin; Fariba Sadat Agha Seyyed Esmaeil Amiri; Kosar Ghaddaripouri; Navid Noroozi; Mohammad Reza Mazaheri Habibi (Wolters Kluwer Medknow Publications, 2023)
Epilepsy is the most common chronic neurologic disease which is characterized by recurrent attacks of headache after seizure. Researches show that self-management is an important factor in improving the quality of life and quality of care of people affected by epilepsy. Mobile phone technologies play a potential role in patient care assistance and treatment of epilepsy. This systematic review was conducted with an aim to study the role of mobile health in the management of epilepsy. This study was conducted by searching databases such as PubMed, Scopus, Web of Science, and Google scholar search engines using the following keywords: "m-health," "mobile health," "Telemedicine," "Mobile Application," "Smartphone," "epilepsy," and "epilepsy management." Articles published from January 1, 1990 to September 1, 2021 were searched. Inclusion criteria included all articles published in English with a focus on the role of mHealth in the management of epilepsy. Review articles and studies that were not about patients were omitted. In this study, of a total of 4225 retrieved articles, 10 studies met the full-text inclusion criteria. Three types of researches (30%) were done in the USA, five studies (50%) were conducted as randomized controlled trials, and eight articles (80%) had the highest quality. Among the considered articles, three articles (30%) were engaged in training users in epilepsy management. Five articles (50%) reported improvement in seizure control in patients with epilepsy and two articles (20%) did not report any significant improvement. Mobile technologies have a promising role in providing health assessment, education, and other services for patients, and they also help in controlling seizures attack and improvement of epilepsy management. These technologies enjoy great attractiveness, and utilizing them will lead to patient satisfaction.